2019
DOI: 10.1007/s41669-019-00179-6
|View full text |Cite
|
Sign up to set email alerts
|

Budget Impact Analysis of Metformin Sustained Release for the Treatment of Type 2 Diabetes in The Netherlands

Abstract: Background Adverse drug reactions and medication nonadherence are well-known causes of sub-optimal disease control and worsened disease outcomes in patients who are treated for type 2 diabetes. Metformin sustained release (SR) might reduce these adverse events and improve medication adherence via a simplified treatment regimen for metformin immediate release (IR)-intolerant patients. Objectives The aim of this study is to estimate the budget impact of metformin SR for the treatment of type 2 diabetes in the Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The discounting rate was not always clearly reported in the included BIA studies. Four studies reported the discounting rate ranging from 3 to 5% (16,(23)(24)(25), eight studies (11,15,(17)(18)(19)(20)(21)27) did not consider the discounting rate in compliance with the ISPOR Task Force guidelines (7). Meanwhile, six studies (10, 12-14, 22, 26) did not mentioned the discounting rate in the articles.…”
Section: Methodology and Budget Results Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…The discounting rate was not always clearly reported in the included BIA studies. Four studies reported the discounting rate ranging from 3 to 5% (16,(23)(24)(25), eight studies (11,15,(17)(18)(19)(20)(21)27) did not consider the discounting rate in compliance with the ISPOR Task Force guidelines (7). Meanwhile, six studies (10, 12-14, 22, 26) did not mentioned the discounting rate in the articles.…”
Section: Methodology and Budget Results Of Biasmentioning
confidence: 99%
“…Among the five basal insulin BIA studies, one of them was about insulin glargine biosimilar (13). The rest of BIA studies targeted GLP-1 RA (n = 4, including once-weekly semaglutide, oral semaglutide, and benaglutide) (12,14,25,27), DPP-4i (n = 3, including vildagliptin, saxagliptin, and linagliptin) (10,15,23), SGLT-2i (n = 2, both were dapagliflozin) (11,17) and metformin (n = 1) (19).…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of current therapies are not just escalating the diabetes prevalence but also crossing the limits of economical budget. All these effects are demanding safer, efficient, easy to administrate, and budget-friendly treatment [ 5 ]. The traditional approach of treatment involves antidiabetic compounds from different plant species, and it is catching more and more attention as natural drugs show fewer side effects compared to synthetic drugs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metformin is inexpensive but causes gastrointestinal side effects in up to 25% of patients (2). Extended-release (ER) formulations reduce side effects but may cost more, and they have not been clearly shown to improve adherence in routine practice (3). As a result, although it is common practice to change from immediate release (IR) formulations to ER once patients develop side effects, there is not a consensus on whether ER formulations should routinely be used when metformin is first prescribed (3).…”
mentioning
confidence: 99%